THE APPLICATION OF THE ROUGH SET METHOD TO ANALYZE THE CONTRIBUTION OF MANAGEMENT OF SCIENCE LABORATORY USE TO STUDENTS' SCIENCE PROCESS SKILLS - Nurhayati; Baharis Setia Adisahputra Simatupang; R.A Fattah Adrianyah; R L Harmady Tamba (Cattleya Darmaya Fortuna, 2023)
This study aims to analyze and determine the operational contribution of laboratory management to students' scientific process skills with Data Mining in collecting data from questionnaire instruments using methods rough set into rosetta software to produce a Decision system in the form of Equivalence Class and Dicernibility Matrix Modulo D Then carry out a Reduction process which will be used as a reference for making General Rules, so as to produce value the highest is SMP N 2 L. Pakam with a percentage of 0.95625 and the result is Good.